Estimating the morbidity and mortality associated with infections due to multidrug-resistant bacteria (MDRB), France, 2012. Issue 1 (December 2016) - Colomb-Cotinat, M.; Lacoste, J.; Brun-Buisson, C.; Jarlier, V.; Coignard, B.; Vaux, S.
Abstract Background A study based on 2007 data estimated that 386, 000 infections due to multidrug-resistant bacteria (MDRB) occurred in Europe that year and 25, 000 patients died from these infections. Our objective was to estimate the morbidity and mortality associated with these infections in France. Methods The MDRB considered were methicillin-resistantStaphylococcus aureus (MRSA), glycopeptide-resistantenterococci, third-generation cephalosporin-resistant (3GC-R)Escherichia coli andKlebsiella pneumoniae, carbapenem-resistantKlebsiella pneumoniae, Acinetobacter spp. andPseudomonas aeruginosa (CRP. aeruginosa ). The number of invasive infections (infections with bacteria isolated from blood or cerebrospinal fluid) due to MDRB, as reported by France to EARS-Net in 2012, was corrected for the coverage of our surveillance network and extrapolated to other body sites using ratios from the French healthcare-associated infections point prevalence survey and the literature. Mortality associated with MDRB infection was estimated using proportions from the literature. Methods and parameters were reviewed by a panel of experts. Results We estimate that 158, 000 (127, 000 to 245, 000) infections due to MDRB occurred in 2012 in France (incidence: 1.48 to 2.85 per 1000 hospital days), including 16, 000 invasive infections. MRSA, 3GC-RE. coli andK. pneumoniae were responsible for 120, 000 (90, 000 to 172, 000) infections, i.e., 75% of the total. An estimated 12, 500 (11, 500 to 17, 500) deaths were associated with these infections, including 2, 700 associated with invasive infections. MRSA, 3GC-RE. coli and CRP. aeruginosa accounted for 88% of these deaths. Conclusion These first estimates confirm that MRSA, 3GC-REscherichia coli andKlebsiella pneumoniae account for the largest portion of the morbidity and mortality of infections due to MDRB in France. These results are not directly comparable with the European study because the methodology used differs in many respects. The differences identified between our study and previous studies underline the need to define a standardised protocol for international assessments of the morbidity and mortality of antibiotic resistance. Estimating morbidity and mortality will facilitate communication and awareness in order to reinforce adherence and support of healthcare professionals and policy-makers to MDRB prevention programs.